Дескриптивна модель забезпечення розвитку внутрішнього ринку товарів - Мардус, Наталія Юріївна (Видавничий дім "Гельветика", 2019)
У статті запропоновано дескриптивну модель забезпечення розвитку внутрішнього ринку товарів, яка відбиває сутність забезпечення розвитку внутрішнього ринку товарів як багато-ітераційного процесу, що складається з послідовно здійснюваних етапів, кінцевою метою яких є досягнення запланованої зміни коефіцієнтів розвитку внутрішнього ринку товарів. Базуючись на основі розробленої структуризації забезпечення розвитку внутрішнього ринку товарів і дескриптивної моделі забезпечення розроблено методичний підхід до забезпечення розвитку внутрішнього ринку товарів, що включає формування бази та системи забезпечення, а також розробку та реалізацію стратегії забезпечення розвитку внутрішнього ринку товарів, вибір виду якої, дозволяє на основі визначення показників стратегічного орієнтування за векторами розвитку прийняти обґрунтоване рішення щодо визначення стратегічних ініціатив та встановлення стратегічних пріоритетів, реалізація яких дозволить досягти поставлених цілей забезпечення.

The article analyzes the main aspects of the strategic development of the internal market of goods. To achieve the goal, it is proposed to construct a descriptive model for ensuring the development of the domestic commodity market. The proposed descriptive model reflects the essence of ensuring the development of the internal market of goods as a complex iterative process. This process consists of successive stages, the ultimate goal of which is to achieve the planned change in the coefficients of development of the domestic market of goods. Implementation of this process, which will improve the state of development of the internal market of goods. The structuring of strategic support for the development of the domestic market of goods with the indication of vectors is carried out. The proposed vectors determine the direction of ensuring the development of the domestic market. Based on the structuring of the provision of the development of the domestic market of goods and the descriptive model of provision, a methodical approach has been developed to ensure the development of the internal market of goods. This methodological approach includes the establishment of a base and a system of provision, as well as the development and implementation of a strategy for the development of the internal market of goods. The choice of a strategy for ensuring the development of the internal market of goods allows us to base a decision on the basis of determining the indicators of strategic orientation according to the development vectors. Thus, the formation of the base according to the conceptual component should include the definition of principles, methodological approaches, the choice of methods of provision, and according to the organizational-diagnostic component – the formation of a regulatory, information, evaluation base. A system of provision was also created according to the target and content component. The implementation of the proposed measures will enable the identification of strategic initiatives and the establishment of strategic priorities, implementation of which will allow achieving the objectives of ensuring the internal market of goods.
Descriptive model of ensuring the development of the internal market of goods
Keywords: модель; прогноз; ринок; забезпечення; розвиток; model; forecast; market; provision; development